Evaluación de la calidad de obturación, restauración y estado periapical de pulpectomías realizadas en una facultad de odontología, 2019-2022. - Flores Guerra, Marcelo (2025)
Objective: To establish the relationship between the quality of filling, restoration and periapical status of pulpectomies performed at the UNAP Faculty of Dentistry between 2019-2022. Method: This research was quantitative, non-experimental, cross-sectional, correlational, retrospective-prospective; having as a sample 85 teeth (24 people). The quality of the filling was evaluated based on the parameters of length (De Moor RJ) and density (Dougas). Restoration quality was assessed according to Ryge's modified criteria from the United States Public Health Service (USPHS) and periapical status was assessed by the Ørstavik Periapical Index (PAI). Results: It was found that the success of treatments performed based on periapical status reached 41.2%; and 58.8% were failures. Likewise, it was determined that there is a relationship between the quality of the filling and the periapical state (p=0.016), but there is no relationship between restoration quality and periapical status (p=0.230). There is a relationship between the length of the filling and periapical state (p=0.022), between the density of the filling and the periapical state (p=0.015), between the material and quality of the restoration (p=0.000) and between the size of the lesion and the periapical state (p=0.000). Conclusions: Pulpectomies performed at the UNAP School of Dentistry between 2019-2022 presented a higher failure rate, being related to the quality of the filling, but not to the quality of the restoration.